NATURAL LANGUAGE PROCESSING WITH TRANSFORMERS - TUNSTALL LEWIS; LEANDRO VON WERRA; THOMAS WOLF (CALIFORNIA O'REILLY SPD PVT LTD, 2023)
"Natural Language Processing with Transformers," authored by Lewis Tunstall, Leandro von Werra, and Thomas Wolf, serves as a comprehensive and practical guide for data scientists and machine learning engineers on applying state-of-the-art Transformer models to real-world Natural Language Processing tasks. Centered almost entirely on the powerful Hugging Face ecosystem$1 (Ba library the authors helped build$1 (Bthe book moves beyond theory to provide hands-on instruction for the complete model lifecycle. It meticulously walks readers through loading data, tokenization, and fine-tuning powerful pre-trained models like BERT and GPT for a wide variety of applications, including text classification, named entity recognition (NER), question answering, and text summarization. Furthermore, it addresses the critical, real-world challenges of deploying models to production, covering essential optimization techniques such as knowledge distillation and quantization to make models smaller and faster.s
NLP
AIML
CSD & CSM & CSC
Keywords: AIML; COMPUTERS